Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5937/ffr1902179s
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acid profiles of honey samples from Vojvodina (Republic of Serbia)

Abstract: Amino acid profile of four honey typestwo monofloral (acacia and sunflower), one polyfloral (meadow honey) and forest honey (honeydew honey) collected from the Autonomous Province of Vojvodina (Republic of Serbia) was determined using ion exchange chromatography. The results showed that proline was the dominant amino acid in all analyzed samples. Other amino acids present in substantial amounts were glutamic acid ˃ phenylalanine ˃ glycine  serine in acacia and meadow honey samples, while sunflower was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In these studies, physicochemical parameters (Devillers, Morlot, Pham-Delègue & Doré, 2004;Acquarone, Buera & Elizalde, 2007;Kirs, Pall, Martverk, & Laos, 2012;Juan-Borrás et al, 2014;Karabagias et al, 2014;El Sohaimy, Masry & Shehata, 2015;Da Silva et al, 2016), carbohydrate profiles (Kaškonienė, Venskutonis & Čeksterytė, 2010;Escuredo et al, 2014;Živkov Baloš, Popov, Prodanov Radulović, Stojanov & Jakšić, 2020), mineral content (Lazarević, 2016;Mračević, Krstić, Lolić & Ražić, 2020), amino acid composition (Sakač et al, 2019), phenolic content (Sari & Ayyildiz, 2012;Alqarni, Owayss, & Mahmoud, 2012;Cimpoiu, Hosu, Miclaus, & Puscas, 2013), volatile compounds (Juan-Borrás et al, 2014) have been suggested as criteria for the characterization of honeys.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, physicochemical parameters (Devillers, Morlot, Pham-Delègue & Doré, 2004;Acquarone, Buera & Elizalde, 2007;Kirs, Pall, Martverk, & Laos, 2012;Juan-Borrás et al, 2014;Karabagias et al, 2014;El Sohaimy, Masry & Shehata, 2015;Da Silva et al, 2016), carbohydrate profiles (Kaškonienė, Venskutonis & Čeksterytė, 2010;Escuredo et al, 2014;Živkov Baloš, Popov, Prodanov Radulović, Stojanov & Jakšić, 2020), mineral content (Lazarević, 2016;Mračević, Krstić, Lolić & Ražić, 2020), amino acid composition (Sakač et al, 2019), phenolic content (Sari & Ayyildiz, 2012;Alqarni, Owayss, & Mahmoud, 2012;Cimpoiu, Hosu, Miclaus, & Puscas, 2013), volatile compounds (Juan-Borrás et al, 2014) have been suggested as criteria for the characterization of honeys.…”
Section: Introductionmentioning
confidence: 99%